Acute-onset paraneoplastic cerebellar degeneration secondary to neuroendocrine carcinoma with atypical prognosis: a case report. Issue 2 (February 2021) - Wang, Kunyu; Miao, Yan; Ning, Haoyong; Guo, Feng; Bian, Yang; Wang, Qingqing; Sun, Chenjing; Qi, Xiaokun; Qiu, Feng
Paraneoplastic cerebellar degeneration (PCD) is a neurological syndrome that is likely caused by tumor-induced autoimmunity against the cerebellum. Neuroendocrine carcinoma (NEC) is a type of neoplasm with high-grade malignant histology and biological behavior. The prognosis for both PCD and NEC is typically poor. We report a case of PCD secondary to metastatic NEC in the lymph nodes, with an unknown primary origin. The case presented acute cerebellar manifestations with typical neuroimaging findings, but with atypical prognosis after lymph node dissection. Neurological symptoms can provide clues to potential tumors, and early antitumor treatment may have contributed to the positive prognosis of PCD secondary to NEC in the present case.